The Organizational Impact of Business Model Innovation: Assessing the Person-Organization Fit - Matthias Menter; Lutz Göcke; Christopher Zeeb (Journal of Management Studies, 2022)
Studies on business model innovation (BMI) have largely focused on firm performance, neglecting outcomes of BMI beyond financial performance indicators. Research lacks empirical findings from the internal organizational dynamics following the inherent transformation process induced by BMI. Rooting our analysis in configuration theory, the purpose of this paper is to shed light on the organizational impact of BMI. We employ the person-organization fit concept and assess (unintentional) changes in the fit relationship subsequent to BMI. Our findings suggest that incremental BMI enhances fit whereas radical BMI decreases it. We further discuss the theoretical and practical implications of our study.
Keywords: 650; business model innovation; organizational impact; configuration theory; momentum period; transition period; person-organization fit